PENGARUH PROMOSI KESEHATAN MELALUI AUDIO VISUAL TERHADAP PENGETAHUAN TANDA BAHAYA KEHAMILAN - Sukarsih, Rachmawati Ika (Sinar : Jurnal Kebidanan, 2023)
Objective: According to WHO, the maternal mortality rate in the world is 303,000 people. The maternal mortality rate in ASEAN is 235/100,000 live births. Low knowledge of mothers regarding danger signs of pregnancy is one of the factors causing the increase in MMR.The purpose of this study was to determine the effect of health promotion through audio visual media in increasing mother’s knowledge about danger signs of pregnancy.Methods: The type of research used is quantitative research with a pre-experimental design, using a one-group pretest-posttest design approach without a control group. The population in this study were 70 primigravida mothers who were processed using probability sampling technique and used random sampling to obtain a total sample of 59 primigravida mothers. Data collection techniques used primary data by filling out questionnaires. This study used the Wilcoxon Test.Results: The results of this study indicated that before carrying out health promotion through audio visual media, knowledge is in the Less category (57.6%) and after being given health promotion, knowledge becomes good by (88.1%). Based on these data, it can be concluded that the use of audio visual media for danger signs of pregnancy can increase the knowledge of primigravida mothers because audio visual media can absorb as much as 50% of memory and stimulate the senses of hearing and vision so that the results obtained are maximized. From the results, it can be concluded there was an increase in the knowledge of primigravida mothers as evidenced by the results obtained. If the P value = 0.000, so P value < 0.05. It means that health promotion through audio visual media has an influence on increasing the knowledge of primigravida mothers at TPMB Muarofah Surabaya. Conclusion: The knowledge of primigravida mothers has increased after carrying out health promotion through the audio visual media of danger signs in pregnanc